Analysis of LC-LC2 Compensated Inductive Power Transfer for High Efficiency and Load Independent Voltage Gain - Alam, Md Morshed; Mekhilef, Saad; Bassi, Hussain; Rawa, Muhyaddin (MDPI, 2018)
A novel LC-LC2 compensated resonant converter topology with high efficiency and good controllable voltage gain is presented in this paper. An additional receiving side inductor working together with the receiving coil has the contribution to work with a large range of air gap distance. Due to this property, proposed compensation technique is effective for IPT based EV charging application. Voltage gain with independent of load and input impedance having ZPA of the proposed resonant converter are observed by the frequency domain analysis. On the other hand, time domain analysis gives the circuit operation. A500WLC-LC2 compensated resonant converter prototype is built to testify the theoretical analysis. To observe the efficiency-comparison, an S-SP compensated resonant converter with a similar amount of output power under different air gap is also presented. In order to justify the effectiveness, the proposed compensation method is verified by the laboratory results. The highest efficiency of the proposed compensated resonant converter is 93% with output power of 500Wat 140-mm air gap between the two sides of the IPT (inductive power transfer) transformer.